Health waste management in the hospital context: an analysis of the knowledge of health professionals (Research, Society and Development, 2022)
Introduction: The knowledge of health professionals about Health Service Waste Management (HSW) contributes to the quality of life of the population and the environment. So, the objective is to analyze the knowledge of health professionals about (HSW) management in the hospital context. Methodology: This is a descriptive, quantitative study. The survey consisted of 151 professionals. Data were collected through a structured questionnaire in accordance with current legislation. The Jasp software was used for data analysis, and descriptive statistical analysis was used, using measures of central tendency and the respective measure of dispersion for continuous variables and absolute and relative frequencies for categorical variables. Values of p < 0.05 were considered statistically significant. Results: Most subjects are female (84.8%), aged between 31 and 40 years (39.7%), with incomplete higher education to graduate school (51%), with length of time in hospital from 1 to 10 years (62.9%) and nursing technicians (55.6%). Of the total, 136 (90.0%) know the (HSW) and 92 (60.9%) know the HCWMP. A significant difference was found in terms of knowledge about (HSW) management between genders (p=0.003), age (rô= -0.167; p=0.041) and intra-hospital sectors (p= 0.008; p=0.018). conclusion: Continuing education is a fundamental strategy to make the level of knowledge among health professionals satisfactory and this reflects on the quality of (HSW) management, and consequently reduces the generation of waste and financial resources, contributing to environmental and collective health.